2011
DOI: 10.1007/s12311-011-0265-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Spinocerebellar Ataxia Type 2 in Cuba

Abstract: Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominant cerebellar ataxia characterized by a progressive cerebellar syndrome associated to saccadic slowing, peripheral neuropathy, cognitive disorders, and other multisystem features. SCA2 is caused by the abnormal expansion of cytosine-adenine-guanine triplet repeats in the encoding region of the ATXN2 gene and therefore the expression of toxic polyglutamine expansions in the ataxin 2 protein, which cause progressive neuronal death of Purkinje cells in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 98 publications
0
68
0
Order By: Relevance
“…Cerebellar degeneration in individuals with SCA2 can therefore affect postural control. It has also been suggested that postural instability is one of the main signs of SCA2 and leads to balance deficits and, consequently, limitations on the individual's ability to perform activities of daily living 17 . The ability to maintain balance is an integral part of gross motor skills, and poor balance and inadequate posture result in difficulties performing activities of daily living 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar degeneration in individuals with SCA2 can therefore affect postural control. It has also been suggested that postural instability is one of the main signs of SCA2 and leads to balance deficits and, consequently, limitations on the individual's ability to perform activities of daily living 17 . The ability to maintain balance is an integral part of gross motor skills, and poor balance and inadequate posture result in difficulties performing activities of daily living 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Overt dystonia and marked cognitive impairment are present in a minority of patients. Bulbar and autonomic signs correlate with the disease duration, pyramidal signs with the CAG size, while the cerebellar features and peripheral neuropathy with both 8, 22, 36, 37…”
Section: Clinical Featuresmentioning
confidence: 97%
“…If we consider that mean age for the onset of the disease is 33 years (Velázquez et al 2011), it is possible that many affected patients had gotten descendants before the PND was available. Though, it could also be the result of the reduction in their fitness once the cerebellar syndrome begun.…”
Section: Prenatal Diagnosis For Sca2: What Have We Learned?mentioning
confidence: 99%
“…It is an adult-onset neurodegenerative condition mainly characterized by a progressive cerebellar syndrome (ataxic gait, cerebellar dysarthria, dysmethria, and dysdiadochokinesia) associated with saccadic slowing, peripheral neuropathy, and cognitive disorders (Velázquez et al 2009(Velázquez et al , 2011Magaña et al 2013).…”
Section: Introductionmentioning
confidence: 99%